Peningkatan Keterampilan Ibu Rumah Tangga Desa Glagaharum melalui Pelatihan Desain Menjadi Pakaian Berbasis Entrepreneurship - Lainardy, Jesslyn Eunice; Balqis, Raissa Ariella Shafa; Tjioe, Vincentia Jennifer Evelyn; Sitepu, Sri Nathasya Br (Universitas Nusantara PGRI Kediri, 2025)
Glagaharum Village in Sidoarjo has untapped economic potential. Some residents earn below the minimum wage. Housewives have sewing skills but are less able to change product designs. Limited knowledge of fashion design and business is a major obstacle. The